2014
DOI: 10.15625/0866-7160/v35n4.3770
|View full text |Cite
|
Sign up to set email alerts
|

Study on the section Trifoliolata DC. (Jasminum L. - Oleaceae Juss.) in Vietnam

Abstract: Jasminum L. compcises about 200 species in the world including 5 sections: Jasminum Green, Alternifolia DC., Trifoliolata DC., Primulina Green and Unifoliolata DC. they distributed in tropical and subtropical in South East Asia, Europa, Australia and Africa. Section Trifoliolata DC. was published by De Candolle (1844) with the typus Jasminum didymum G. Forst. and characterized by leaves 3-foliolate, terminal leaflet slightly larger than or equal to lateral leaflets or sometimes, lateral leaflets reduced. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…During field explorations, the first author collected many woody climbers (lianas) from the study area of which five were found uncommon ones. After critical morpho-taxonomic examination of all the specimens, scrutiny of relevant literature (Hooker 1875-83;Kanjilal et al 1934-39;Fang & Staples 1995;Chang et al 1996;Chen & Turland 2007;Quang et al 2013;eFlora 2017) and matching of specimens housed in herbaria of Botanical Survey of India (BSI), Eastern Regional Centre, Shillong (ASSAM) and Central National Herbarium (CNH), Howrah (CAL), the species were identified as Ampelopsis rubifolia (Wall.) Planch.…”
Section: Platinum Open Accessmentioning
confidence: 99%
“…During field explorations, the first author collected many woody climbers (lianas) from the study area of which five were found uncommon ones. After critical morpho-taxonomic examination of all the specimens, scrutiny of relevant literature (Hooker 1875-83;Kanjilal et al 1934-39;Fang & Staples 1995;Chang et al 1996;Chen & Turland 2007;Quang et al 2013;eFlora 2017) and matching of specimens housed in herbaria of Botanical Survey of India (BSI), Eastern Regional Centre, Shillong (ASSAM) and Central National Herbarium (CNH), Howrah (CAL), the species were identified as Ampelopsis rubifolia (Wall.) Planch.…”
Section: Platinum Open Accessmentioning
confidence: 99%
“…Green (1993) in one of his publications, cited these gatherings as syntypes. A survey of literature and multiple herbaria revealed that a lectotype for J. sinense has not been designated in earlier studies (Green 1993, and Bui et al 2013. While looking for the original materials, we found eight specimens of these collections deposited in IBSC, K, P and US (IBSC0002797, K000901323, K000901324, K000901325, K000901326, P00640606, P00640607 and US00112856).…”
mentioning
confidence: 93%